Molecular dynamics simulations of disordered materials : from network glasses to phase-change memory alloys /: from network glasses to phase-change memory alloys. ([2015]) - Massobrio, C (Carlo); Du, Jincheng; Bernasconi, Marco; Salmon, P (Philip)
No abstract available